2020
DOI: 10.1111/1365-2664.13660
|View full text |Cite
|
Sign up to set email alerts
|

Declining invasive grey squirrel populations may persist in refugia as native predator recovery reverses squirrel species replacement

Abstract: Invasive species pose one of the most serious global threats to biodiversity. Investigations into the interactions of native and non‐native species focus on the impacts of single species, despite being embedded in a network of direct and indirect interactions between multiple species and their environments. We developed 1‐km2 resolution, single‐species and multi‐species occupancy models using quantitative camera trap data collected by citizen scientists at 332 sites in a regional survey comprising the 14,130 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 82 publications
0
38
1
Order By: Relevance
“…The European pine marten Martes martes is a small carnivore currently recovering in Britain and Ireland following severe historical decline driven by habitat loss and persecution (Langley and Yalden 1977, O'Mahony et al 2017, Sainsbury et al 2019. Recent research demonstrates the species may be limited by human disturbance to the more remote, forested parts of Europe (Balestrieri et al 2019, Twining et al 2020. There is some evidence that it is the structural elements of ancient forest that are required, not the presence of old-growth forest per se (Brainerd et al 1995, Caryl et al 2012.…”
mentioning
confidence: 99%
“…The European pine marten Martes martes is a small carnivore currently recovering in Britain and Ireland following severe historical decline driven by habitat loss and persecution (Langley and Yalden 1977, O'Mahony et al 2017, Sainsbury et al 2019. Recent research demonstrates the species may be limited by human disturbance to the more remote, forested parts of Europe (Balestrieri et al 2019, Twining et al 2020. There is some evidence that it is the structural elements of ancient forest that are required, not the presence of old-growth forest per se (Brainerd et al 1995, Caryl et al 2012.…”
mentioning
confidence: 99%
“…This study used data collected by citizen science to show that red squirrel occupancy was positively correlated with coniferous woodland and negatively correlated with urban habitat. Likewise, grey squirrels were positively correlated with broadleaved forests and urban habitat and negatively correlated with coniferous habitat (Twining et al 2020). The study also found a negative correlation between grey squirrels and pine marten (Martes martes), a native mustelid whose numbers are increasing, and a positive correlation between pine marten and red squirrels.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical studies using a two prey-one predator ecoepidemic model have also shown that the predator (pine marten) can destabilise the previous grey squirrel dominant equilibria, favouring the native red squirrel (Travaglia et al 2020). Thus, the impact of a native predator could aid red squirrel survival in the United Kingdom and Ireland via a reduction in grey squirrel density and geographic spread (Twining et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is because traps can be left in fixed locations on site, and over more defined survey periods. Twining et al (2021) use such data in a study of red (Sciurus vulgaris) and grey squirrel (Sciurus carolinensis), and pine marten (Martes martes) distribution at 332 sites distributed across Northern Ireland.…”
Section: Species Movement and Distributionmentioning
confidence: 99%
“…species presence) in a more planned and systematic way. This is because traps can be left in fixed locations on site, and over more defined survey periods Twining et al (2021). use such data in a study of red (Sciurus vulgaris) and grey squirrel (Sciurus carolinensis), and pine marten (Martes martes) distribution at 332 sites distributed across Northern Ireland.Camera trap data were used to build species occupancy models and demonstrated that the recovery of pine marten was strongly, and positively associated with red squirrel populations, with grey squirrel having the opposite relation.…”
mentioning
confidence: 99%